Changes of dental anxiety, aesthetic perception and oral health-related quality of life related to influencing factors of patients' demographics after anterior implant treatment: a prospective study - Xin Xie; Zhengchuan Zhang; Jing Zhou; Feilong Deng (SpringerOpen, 2023)
Abstract Background Accumulating evidence has revealed the effects of anterior implant procedures on dental anxiety (DA), aesthetic perception and oral health-related quality of life (OHRQoL). However, few reported the changes and influencing factors of the above outcomes before and after anterior implant treatment. This study was to evaluate the changes of DA, aesthetic perception and OHRQoL related to influencing factors of patients' demographics after anterior implant treatment. Methods Thirty-nine patients satisfying the inclusion criteria were prospectively recruited before surgery. The subjects completed the Modified Dental Anxiety Scale (MDAS), the Orofacial Esthetic Scale (OSE) and the Oral Health Impact Profile-14 (OHIP-14), before implant surgery and after definitive prosthesis placement. Mann-Whitney U test and Kruskal-Wallis test by Bonferroni correction were applied for the data analysis and the influencing factors evaluation (p < 0.05). Results Overall, 39 patients (mean age of 44.9 ± 12.0) completed the three scales. After anterior implant treatment, MDAS was not significantly changed (p > 0.05). The overall OSE (p < 0.001) and OHIP-14 (p < 0.05) were significantly improved. Females showed more improvement of overall OHIP score than males after anterior implant treatment (p < 0.05). Conclusions Anterior implant procedures did not change the level of patient's DA, while aesthetic perception and OHRQoL were enhanced. Only gender difference of overall OHIP change was found in our study. Thus, more related influencing factors with larger sample and long-term effective follow-up are needed. Trial registration: ClinicalTrials.gov, NCT05424458. Registered 13 June 2022-Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT05424458 .